2016
DOI: 10.1103/physrevlett.116.227401
|View full text |Cite
|
Sign up to set email alerts
|

Photon-Assisted Shot Noise in Graphene in the Terahertz Range

Abstract: When subjected to electromagnetic radiation, the fluctuation of the electronic current across a quantum conductor increases. This additional noise, called photon-assisted shot noise, arises from the generation and subsequent partition of electron-hole pairs in the conductor. The physics of photon-assisted shot noise has been thoroughly investigated at microwave frequencies up to 20 GHz, and its robustness suggests that it could be extended to the terahertz (THz) range. Here, we present measurements of the quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…The studied systems cover different new features of photon-assisted quantum transport occurring into the GHz and THz frequency spectra. Actually, measurements of the quantum shot noise in a graphene nanoribbon subjected to electromagnetic THz radiation were recently reported [27], indicating that the studied bilayer graphene flake system may be realized and proposed as THz frequency detector devices.…”
Section: A)-(d) the Weighted Spin Polarization Exhibits The Same Behmentioning
confidence: 99%
“…The studied systems cover different new features of photon-assisted quantum transport occurring into the GHz and THz frequency spectra. Actually, measurements of the quantum shot noise in a graphene nanoribbon subjected to electromagnetic THz radiation were recently reported [27], indicating that the studied bilayer graphene flake system may be realized and proposed as THz frequency detector devices.…”
Section: A)-(d) the Weighted Spin Polarization Exhibits The Same Behmentioning
confidence: 99%
“…[88,91], the greater and lesser Green's functions were expressed in terms of the S α matrices following a line integral of the Kadanof-Baym equations in the two-time plane, and these are given in Eq. (25). We thus have explicit formulas for all terms which appear in the two-time correlation function, which may be evaluated numerically in the (t 1 ,t 2 ) plane as follows:…”
Section: Time-dependent Model and The Wblamentioning
confidence: 99%
“…Recent measurements of shot noise in graphene irradiated by THz fields showed an enhancement of the shot noise due to the excitation of electron-hole pairs in the sample [25].…”
Section: Introductionmentioning
confidence: 99%
“…55. In the context of graphene, photonassisted shot noise was recently measured in the diffusive electron transport regime 56 . It was shown that shot noise signatures of radiation in this system could be extended to the higher THz frequency range.…”
Section: Introductionmentioning
confidence: 99%